Improving Leadership Decision-Making (LDM) through Knowledge Management (KM) in Public Sector (PS) of Pakistan - Salam, Muhammad Abdus; Haq, Naveed ul (Journal of Public Policy Practitioners, 2024)
The current study aimed to identify the existing leadership decision-making (LDM) in the public sector (PS) of Pakistan along with its role, barriers, constraints, and issues. Thereafter, the study attempted to examine the application of knowledge management (KM) principles and techniques for the augmentation of LDM to enhance the overall efficacy of PS. The study was qualitative in nature and comprised rigorous literature review and examination of archival records of PS in Pakistan. Additionally, it also analyzed the personal insights and reflections from the PS of Pakistan. The findings revealed that the field is in embryonic stage and requires extensive research in qualitative as well as quantitative domain. There is even a lack of basic awareness pertaining to KM and its subfields encompassing tacit knowledge, explicit knowledge, and phronesis. However, the growth of private sector and the role of key decisions taken by the leadership in shaping their sustainable success is a prime lesson to be learnt by the PS in terms of adoption of KM for better decision-making (DM). Moreover, the study also focused on the development of a model by modifying an existing DM organizational model presented in 2017. However, generalizability could be an issue, since this study was conducted based on the personal reflections of the researcher. Additionally, empirical validation, quantitative, longitudinal, cross-sectional, and case study researches may b conducted to evaluate the implications of the study. PS is considered as a non-profit organizational setup. There is a wide gap between public and private sector due to the difference in the role played by both. However, a number of practices can be adopted interchangeably to improve and enhance the existing capabilities which in case of PS include governance, compliance, and citizen satisfaction. The current study provided theoretical insights into how KM models, themes, and practices can be applied for the improvement of DM in the PS. The model presented was novel and an addition to the existing body of knowledge.